Penguatan Kapasitas Kelurahan dalam Penyusunan Perencanaan dan Penganggaran Responsif Gender di Kota Surakarta - Indra Kertati; Setyohadi Pratomo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Gender Mainstreaming is a development strategy for achieving gender equality by integrating gender perspectives into every stage of planning, implementation, monitoring, and evaluation. One key instrument is Gender-Responsive Planning and Budgeting (GRPB). However, village-level officials often have limited capacity to use sex-disaggregated data, identify gender issues, and prepare Gender Analysis Pathway (GAP) and Gender Action Budget (GAB) documents. This community service program aimed to strengthen the capacity of urban village officials in Surakarta City to prepare applicable GRPB documents. The program involved representatives from 54 urban villages through technical assistance, mentoring, interactive lectures, group discussions, case studies, GAP and GAB practice, and individual consultations. The mentoring used a four-step GAP model covering gender data and issue identification, causal analysis, action plan formulation, and determination of relevant implementing institutions. The results showed improved participants’ understanding of gender concepts, social inclusion, gender-responsive budgeting, and technical preparation of GAP and GAB documents. Participants were able to identify local gender issues and formulate action plans aligned with village development priorities. The program also strengthened awareness of sex-disaggregated data as evidence for inclusive planning and demonstrated that capacity building supports gender-responsive local development at the urban village level in a sustainable and participatory manner effectively.